DEVELOPING A COMMUNITY SAFETY SCORECARD: USING SMALL AREA DESIGNATIONS TO DESCRIBE RISK AND PROTECTIVE FACTORS AND INEQUITIES ACROSS A LARGE URBAN AREA. (7th October 2012) - Weiss, B; Meza, M; Lee, S; Hsu, P; Rice, C
Abstract : Background: Despite downward cascading crime rates, many communities have extraordinarily high rates of gang violence and other violent crime. Children in these communities experience victimisation or witness crime and violence on a daily basis. Aims/Objectives/Purpose: To understand neighbourhood disparities in safety and community equity, the Violence Prevention Coalition and the Advancement Project created a Community Safety Scorecard, 'snapshot', of risk and protective factors to compare neighbourhoods and communities within Los Angeles. Methods: Approximately 1400 indicators identified as relevant to community safety. Using regression analyses four domains were identified with the greatest correlation to desired outcomes. These domains are; community safety, risk-factors, protective-factors, and school conditions. Three to five indicators in each of the domains provided sufficient information to generate a meaningful score. Indicators were then aggregated and indexed to create a standardised score by 'zip code', and letter grades from A to F, similar to school report cards were assigned. Results/Outcomes: Inequity in public safety and investment was revealed and solutions suggested. Zip-codes with little investment and those in danger of becoming 'hot zones.' were identified. Recommendations for a multi-layered violence reduction model were designed. Significance/Contributions to the Field: The Scorecard helps to identify solutions and provides direction to the type of solutions needed. It shows that focusing attention only on one domain is not sufficient to turn high risk neighbourhoods into safe communities. This methodology is adaptable to other locations and provides a tool for community progress. It calls attention to community inequities and can guide policymakers towards equitable resource distribution.